2019
DOI: 10.3390/nano9040485
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Synthesis of Phosphonic Graphene Derivative and Its Application in Mercury Ions Adsorption

Abstract: Functionalized graphene was efficiently prepared through ball-milling of graphite in the presence of dry ice. In this way, oxygen functional groups were introduced into material. The material was further chemically functionalized to produce graphene derivative with phosphonic groups. The obtained materials were characterized by spectroscopic and microscopic methods, along with thermogravimetric analysis. The newly developed material was used as an efficient mercury adsorbent, showing high adsorption efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…The adsorption isotherm, in accordance with the Langmuir model, shows that the adsorption of pollutants on ball-milled materials is monolayer coverage with a similar energy of adsorption sites [165,166]. The alignment of adsorption kinetics with the pseudo-second-order model indicates that the ball milling brings numerous active sites to materials, and the adsorption kinetics stays in correlation with the availability of adsorption sites on the surface of adsorbents rather than adsorbate concentrations in bulk solution [121]. The best fit of the Redlich-Peterson and Elovich model on Ni(II) adsorption by the ball-milled biochars (BM-BCs) suggested that it was heterogeneous, involving multi-mechanism adsorption processes [86].…”
Section: Removal Of Inorganic Pollutantssupporting
confidence: 56%
See 2 more Smart Citations
“…The adsorption isotherm, in accordance with the Langmuir model, shows that the adsorption of pollutants on ball-milled materials is monolayer coverage with a similar energy of adsorption sites [165,166]. The alignment of adsorption kinetics with the pseudo-second-order model indicates that the ball milling brings numerous active sites to materials, and the adsorption kinetics stays in correlation with the availability of adsorption sites on the surface of adsorbents rather than adsorbate concentrations in bulk solution [121]. The best fit of the Redlich-Peterson and Elovich model on Ni(II) adsorption by the ball-milled biochars (BM-BCs) suggested that it was heterogeneous, involving multi-mechanism adsorption processes [86].…”
Section: Removal Of Inorganic Pollutantssupporting
confidence: 56%
“…And then, defects were changed to oxygen-containing functional groups due to the participation of O 2 from the atmosphere [32]. Olszewski et al [121] indicated that ball milling graphite with CO 2 not only introduced oxygen-containing functional groups into the edges of graphite planes but also prevented the materials from uncontrollable destruction and remained the layered structure with lower defects compared to the one ball milling in air. This method eliminated the use of solvents without by-products and was conductive to converse carboxylic groups into un-hydrolyzed phosphonic groups by reacting with PCl 3 to obtain phosphonic graphene derivatives (PGO) (Figure 4b).…”
Section: Ball-milled Graphene-based Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, adsorption technology is widely used due to its low cost, ease of operation, and high efficiency [ 14 ]. Metal oxides [ 15 ], carbon materials [ 16 ], metalorganic frameworks (MOF) [ 17 ], graphene [ 18 ], zeolites [ 19 ], and polymers [ 20 ] have all been used as adsorbents in the treatment of polluted water. Among them, activated carbon (AC) is one of the most commonly used adsorbents, which is one kind of low-cost adsorbent, and the corresponding adsorption performance is primarily determined by the carbon pore structure, which is derived by the carbon resource and carbonization process.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanochemical method, also known as mechanical alloying, is a convenient solid-state processing technique in which the precursor powders are exposed to repeated welding, fracturing, and re-welding in a high energy ball mill. The method has been developed in the 1970s for the fabrication of nickel- and iron-base superalloys for applications in the aerospace industry [ 32 , 33 ] and is nowadays widely used in the processing of advanced materials like alloys [ 34 ], bimetallic nanocatalysts [ 35 ], oxide materials [ 36 , 37 ], carbon-based materials [ 38 , 39 , 40 ], etc. The first reports of mechanochemical synthesis of metal chalcogenides date back to the 1990s, and since then, a number of nanosized sulfides, selenides, and tellurides have been prepared using this method.…”
Section: Introductionmentioning
confidence: 99%